Effect of Directional Solidification Variables on the Microstructures of Single‐Crystal Turbine Blades of Nickel‐Based Superalloy. Issue 11 (9th June 2017) - Wang, Fu; Wu, Zining; Ma, Dexin; Bührig‐Polaczek, Andreas
Abstract : Single‐crystal turbine blades of nickel‐based superalloy are directionally solidified at different withdrawal rates of 0.0017 cm s −1 –0.01 cm s −1 aiming to investigate the evolution of as‐cast microstructures. The results show that the average primary and secondary dendrite arm spacings, λ 1 ¯ and λ 2 ¯, decrease with increasing withdrawal rate, although the complicated geometry of the blades results in local nonhomogeneity of dendrite arm spacings. The experimentally achieved values of λ 1 ¯ can be reasonably predicted by Ma and Sahm's theoretical model, in which the effect of the secondary dendrite on the primary dendrite arm spacing is considered. With increasing withdrawal rate, the shape of the γ/γ′ eutectic varies from a large block‐like eutectic island to an interconnected small strip‐like morphology. In addition to this, the average size of the γ/γ′ eutectic gradually decreases with increasing withdrawal rate. A reduction in the average sizes of the γ′ precipitates in the dendrite core and interdendritic region is also observed with increasing withdrawal rate. The microsegregation levels of Al, Ti, Ta, Cr, Co, and Mo are alleviated with increasing withdrawal rate. Abstract : SC blades are directionally solidified at various withdrawal rates ( V ) to study the evolution of microstructures. The microstructures are refined with increasing V, although the geometry of blades results in local nonhomogeneous microstructures. λ 1 ¯ can be predicted by Ma and Sahm's model. The microsegregation levels of alloying elements are alleviated with increasing V .